Author Correction: A dataset of 137Cs activity concentration and inventory in forests contaminated by the Fukushima accident - Shoji Hashimoto; Naohiro Imamura; Ayumi Kawanishi; Masabumi Komatsu; Shinta Ohashi; Kazuya Nishina; Shinji Kaneko; George Shaw; Yves thiry (Scientific Data, 2021)
A Correction to this paper has been published: https://doi.org/10.1038/s41597-021-00855-5.